A Case of Ofuji Disease Successfully Treated with the Combination of Low-Dose Indomethacin and Topical Tacrolimus - Claudio Marasca; Angelo Ruggiero; Gabriella Fabbrocini; Matteo Megna (Karger Publishers, 2020)
Eosinophilic pustular folliculitis (EPF) (Ofuji disease) is a chronic, noninfectious pruritic cutaneous disorder of unknown etiology. No official guidelines are available for its treatment. Herein we present the case of a 59-year-old Caucasian man admitted to our outpatient clinic due to a generalized itchy skin rash characterized by papulo-pustules involving the face, trunk, and limbs. Histological examination supported the clinical diagnosis of EPF (Ofuji disease). The combination of low-dose oral indomethacin and topical tacrolimus ointment once a day led to a complete resolution of the lesions as well as associated symptoms in 8 weeks.